Understanding the Interplay between Resilience Capacities and Internal Controls: A Literature Review Perspective - AL SHAKARCHI, Alae; NAFZAOUI, Mohamed Achraf (Revue du contrôle, de la comptabilité et de l’audit, 2024)
In an increasingly interconnected world (society, technology and environment), no organization can sustain a competitive position and survive disruption as an independent and successful entity if it doesn’t adapt its organizational systems. The goal of this review is to provide an overview of the literature in the area of ​​resilience, with regard to the adaptation of the internal control principles and methods. The main question of this paper is: How can the adjustments of the internal control system of a company reinforce its resilience capacities? The relevance of the article is based on the need to gain more knowledge of the relationship between the components of the internal control system and elements of the organizational resilience. The literature review that was handled, showed that there is a lack of research exploring this subject. We examine the relevant literature on organizational resilience and internal control, identifying the main connections between resilience and the components of internal control (Control Environment; Risk Management; Control Activities; Information and communication Monitoring Activities). Our review showed that the adaptation of these components is the key to overcome crises and build on the experience in order to strengthen resilience capacities.